Pseudomonas aeruginosa colonization enhances ventilator-associated pneumonia-induced lung injury. Issue 1 (December 2016) - Tsay, Tzyy-Bin; Jiang, Yu-Zhen; Hsu, Ching-Mei; Chen, Lee-Wei
Abstract Background Pseudomonas aeruginosa (PA) is the single-most common pathogen of ventilator-associated pneumonia (VAP). Large quantities of PA in the trachea of ventilated patients are associated with an increased risk of death. However, the role of PA colonization in PA VAP-induced lung injury remains elusive. This study examined the effect and mechanism of PA colonization in VAP-induced lung injury. Methods C57BL/6 wild-type (WT) and c-Jun N-terminal kinase knockout (JNK1−/− ) mice received mechanical ventilation for 3 h at 2 days after receiving nasal instillation of PA (1 × 106 colony forming unit) or normal saline. Results Intranasal instillation of PA or mechanical ventilation induced the expression of interleukin-6 (IL-6) in the lungs. Phospho-JNK protein expression in the lungs was significantly increased in mice receiving mechanical ventilation after PA instillation as compared with those receiving ventilation alone. Mechanical ventilation after PA instillation significantly increased the expression of tumor necrosis factor-α (TNF-α), IL-1β, and macrophage inflammatory protein-2 (MIP-2) proteins; neutrophil sequestration; and TNF-α, IL-1β, and IL-6 levels in the lungs of WT mice, but not in JNK1−/− mice. Conclusion PA colonization plays an important role in PA VAP-induced lung injury through the induction of JNK1-mediated inflammation. PA-induced VAP causes lung injury through JNK signaling pathway in the lungs. JNK inhibition in ICU patients with higher percentages of PA colonization may reduce VAP-induced lung injury and mortality.